2021
DOI: 10.3390/su132011312
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Japanese Sado Island Farmers’ GIAHS Inclusivity by Understanding Their Perceived Involvement

Abstract: Sado Island in the Niigata prefecture is among the first Globally Important Agriculture Heritage Systems (GIAHSs) in Japan and among developed countries worldwide. Recent studies have pointed out the need to incorporate culture and farmer opinions to further strengthen GIAHS inclusivity in rural farming. In connection to this, this study explored whether farmer visibility, which is highlighted by GIAHS designation, actually translates to farmers’ actual perceptions of GIAHS involvement. A survey was conducted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Japan has been very active in the promotion of sustainable agriculture for several decades, of which the preservation of traditional farming, agro-culture, and biodiversity is highly valued. This enabled Japan's different prefectures to apply and get designated as Globally Important Agricultural Heritage Systems (GIAHS) [21]. The Food and Agriculture Organization of the United Nations (FAO) defined GIAHS as "outstanding landscapes of aesthetic beauty that combine agricultural biodiversity, resilient ecosystems, and a valuable cultural heritage".…”
Section: Farmer Perceptions Of Climate Change and Adoption Of Environ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Japan has been very active in the promotion of sustainable agriculture for several decades, of which the preservation of traditional farming, agro-culture, and biodiversity is highly valued. This enabled Japan's different prefectures to apply and get designated as Globally Important Agricultural Heritage Systems (GIAHS) [21]. The Food and Agriculture Organization of the United Nations (FAO) defined GIAHS as "outstanding landscapes of aesthetic beauty that combine agricultural biodiversity, resilient ecosystems, and a valuable cultural heritage".…”
Section: Farmer Perceptions Of Climate Change and Adoption Of Environ...mentioning
confidence: 99%
“…At present, there are 11 sites designated as GIAHS in Japan. These are in the prefectures of Ishikawa, Niigata, Shizuoka, Kumamoto, Oita, Gifu, Wakayama, Miyazaki, Miyagi, and Tokushima [21]. This paper particularly focused on Sado Island in Niigata prefecture, one of the first GIAHS sites designated in a developed country.…”
Section: Farmer Perceptions Of Climate Change and Adoption Of Environ...mentioning
confidence: 99%
“…However, the adoption of ECA practices is not without challenges. Studies have shown that farmers face various constraints in adopting ECA practices, such as limited access to essential resources that can hinder their acceptance and adoption of ECA [17,18].…”
Section: The Sustainability Of Ecamentioning
confidence: 99%
“…It is closely connected to food culture and societal customs. Various agricultural heritage programs worldwide, such as the farmers' rice cultivation on Sado Island in Japan, known for the Toki branding, encompass a range of crops such as persimmons, apples, pears, cherries, oranges, strawberries, watermelons, and shiitake mushrooms [25]. Similarly, the Xuanhua vineyard culture in China represents another agricultural culture within the GIAHS framework [26].…”
Section: Cultural Capitalmentioning
confidence: 99%